2015
DOI: 10.1016/j.scitotenv.2015.04.118
|View full text |Cite
|
Sign up to set email alerts
|

Binding interactions between suberin monomer components and pesticides

Abstract: Understanding the role of biomacromolecules and their interactions with pollutants is a key for elucidating the sorption mechanisms and making an accurate assessment of the environmental fate of pollutants. The knowledge of the sorption properties of the different constituents of these biomacromolecules may furnish a significant contribution to this purpose. Suberin is a very abundant biopolymer in higher plants. In this study, suberin monomers isolated from cork were analyzed by thermally-assisted methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…the accumulation of DCA in naturally occurring yeasts (Mauersberger et al 1992;Eschenfeldt et al 2003). The degradation of DCA occurred slower for long-chain DCA (C 18 , C 20 , C 22 ), which showed a higher resistance to microbial degradation than those with short and moderate chain lengths (C 2 − 12 ) (Olivella et al 2015;Saxena and Hildemann 1996). Degradation time may be expressed as halflife, defining the time required to degrade half the amount of the specific compound, which was applied and released as CO 2 (Jones and Shannon 1999;Boddy et al 2007;Pearson and Eglinton 2000) estimated mean terrigenous residence times for higher plant wax (C 24 − 33 ) derived long-chain n-alkanes and DCA from sediments to be less than 100 years.…”
mentioning
confidence: 99%
“…the accumulation of DCA in naturally occurring yeasts (Mauersberger et al 1992;Eschenfeldt et al 2003). The degradation of DCA occurred slower for long-chain DCA (C 18 , C 20 , C 22 ), which showed a higher resistance to microbial degradation than those with short and moderate chain lengths (C 2 − 12 ) (Olivella et al 2015;Saxena and Hildemann 1996). Degradation time may be expressed as halflife, defining the time required to degrade half the amount of the specific compound, which was applied and released as CO 2 (Jones and Shannon 1999;Boddy et al 2007;Pearson and Eglinton 2000) estimated mean terrigenous residence times for higher plant wax (C 24 − 33 ) derived long-chain n-alkanes and DCA from sediments to be less than 100 years.…”
mentioning
confidence: 99%
“…For plants, suberin and suberan are the important natural biopolymers. Their role is to provide a protective barrier between the plant and the environment [183]. The structure of this hydrolysable polyester is proposed to be comprised of long chain (C 11 eC 24 ) polymethylenic domains with carboxylic acids held together by aromatic rings and esters [184].…”
Section: Lignin and Plantsmentioning
confidence: 99%
“…The structure of this hydrolysable polyester is proposed to be comprised of long chain (C 11 eC 24 ) polymethylenic domains with carboxylic acids held together by aromatic rings and esters [184]. Olivella [183,185] analyzed the suberin monomers isolated from cork by TMAH-Py-GC/MS. Their study showed that the major compounds of suberin from back and cork layers were octadec-9-enedioic acid, docosanedioic acid, and 9,10-epoxyocta-decanedioic acid with mean values of 17.0%, 14.5%, and 11.0%, respectively.…”
Section: Lignin and Plantsmentioning
confidence: 99%
“…These interact with cork components by establishing π-interactions and hydrogen bonding. 163,164 Biosorbents for Oil Spillages. Another field of application of biosorbents is the sorption of oil and grease from water.…”
Section: ■ Biorsorbents From Corkmentioning
confidence: 99%
“…Also, the adsorption is higher for lower molecular weight PAHs. , On the contrary, the adsorption of aromatic pesticides on cork occurs primarily at the lignin and phenolic extractives level. These interact with cork components by establishing π-interactions and hydrogen bonding. , …”
Section: Biorsorbents From Corkmentioning
confidence: 99%